Effect of pH, Temperature, and Metal Activator on The Activity of Fibrinolytic Enzymes Produced by Pseudomonas Aeruginosa Ts 6.4 - Hanum, Siti Halima; Toto Poernomo, Achmad; Sudjarwo, Sudjarwo; Rosyidah, Shofiatur (Universitas Airlangga, 2022)
Fibrinolytic enzymes were found in several microorganisms, including Pseudomonas aeruginosa TS 6.4, which was isolated from sea cucumbers (Paracaudina australis). Sea cucumbers possessed many pharmacological activities, such as antithrombotic and antihyperlipidemic effects. In addition, fibrinolytic enzymes had been identified in Stichopus japonicus, one of the sea cucumber species. The activity of fibrinolytic enzymes was influenced by pH, temperature, activators, inhibitors, and the concentration of enzyme-substrate. This study aimed to determine the pH and optimum temperature of fibrinolytic enzyme activity of Pseudomonas aeruginosa TS 6.4. The optimum pH was achieved at pH 5-6, while the optimum temperature was reached at 50°C. The effect of the addition of metal activators CaCl2, MnCl2, MgCl2, ZnCl2, and CoCl2 on the activity of fibrinolytic enzymes was also studied. The results showed that the fibrinolytic activity of Pseudomonas aeruginosa TS 6.4 was affected by Ca2+, Mg2+, Mn2+, Zn2+, and Co2+.Keywords: Pseudomonas aeruginosa TS 6.4, Fibrinolytic Enzyme Activity, pH, Temperature, Metal activator